Analisis Fenomenologi Perilaku Komunikasi Etnis Tionghoa Di Kota Batam - Angga Intueri Mahendra (Communicology: Jurnal Ilmu Komunikasi, 2021)
ABSTRACT In a heterogeneous and multi-ethnic city such as in Batam, adaptation in inter-ethnic interactions is a must. Efforts to establish effective inter-ethnic communication can promote harmonious relationships that are built in this urban community group. Although they have lived and lived in Indonesia for a long time in general and Batam City more specifically, the Chinese ethnic community still has the stigma of being an ethnic immigrant. Historical records prove that the relationship between the Chinese ethnic group and various other ethnicities in Indonesia has been established for a long time and has made quite an important contribution to the social and economic life of the community, especially in the city of Batam. This study aims to determine the phenomenon of communication behavior (verbal and non-verbal) between ethnic Chinese and other ethnic groups in Batam city, as well as communication behavior between ethnic groups. An interactive qualitative research approach with phenomenological analysis with the object of research in the PSMTI and BMTI organizations in Batam City. The results showed that the interpersonal verbal communication behavior of the Chinese ethnic community in the family environment generally uses the ethnic languages ​​of each tribe. Meanwhile, the use of Indonesian is used for children's education as well as as a complement and substitute for several language contexts where no equivalent is found in ethnic languages. In both PSMTI and BMTI organizations, the use of Indonesian both orally and in writing is becoming more dominant. Various forms of non-verbal communication for the Chinese ethnic community include the use of red symbols, artifacts in the form of houses of worship and statues, body language such as clenching fists and other forms of non-verbal communication. Keywords: Chinese Ethnicity; Communication Behavior; Phenomenological Analysis